What determines fund performance persistence? International evidence - Ferreira, M. A. (2019)
We study performance persistence across a global sample of equity mutual funds from 27 countries. In contrast to the existing U.S.-based evidence, we find that net performance persistence is present in the majority of fund industries, suggesting that fund manager skill is commonplace rather than a rarity. Consistent with the intuition that more competition in the mutual fund industry makes remaining a winner fund less likely but keeping a loser fund at the bottom of the performance ranks more probable, we show that competitiveness explains the cross-sectional variation in performance persistence.